Entrepreneurial Orientation as Antecedent of Business Model Innovation among Medium Enterprises in Kenya - Albert Kisiang’ani Simiyu; Elijah Bitange Ndemo; Mary Wanjiru Kinoti; Gituro Wainaina (European Scientific Journal, ESJ, 2023)
This study investigated the influence of entrepreneurial orientation on business model innovation in medium enterprises in Kenya. The study was grounded on the dynamic capabilities view. A descriptive cross-sectional survey research design was adopted to achieve the study’s objective. The sampling frame was the Klynveld Peat Marwick Goerdeler (KPMG) East Africa and the Nation Media Group annual Top100 companies in Kenya.  Stratified random sampling was utilized to derive 221 companies that were used in the study. Primary data were collected from single respondents comprising senior managers of the participating firms. A total of 134 questionnaires were analysed. Ordinary least squares regression analysis revealed that entrepreneurial orientation is an antecedent of business model innovation among medium enterprises in Kenya. On the basis of the results, this study concluded that entrepreneurial orientation is necessary for enterprises to benefit from business model innovation. The study recommends that managers of medium enterprises in Kenya embrace entrepreneurial behaviour and attitude to enhance business model innovation practices.   It is further recommended that policymakers should develop and implement policies that encourage innovation and entrepreneurial behaviour. The study clarifies the position of entrepreneurial orientation in relation to BMI. Additional studies are recommended.